Hippocampal volume in patients with asthma: Results from the Dallas Heart Study. (2nd January 2017) - Carlson, Scott M.; Kim, Julie; Khan, David A.; King, Kevin; Lucarelli, Richard T.; McColl, Roderick; Peshock, Ronald; Brown, E. Sherwood
ABSTRACT: Introduction: Asthma is associated with an increased risk of mild cognitive impairment and dementia. Depression and oral corticosteroid use are associated with atrophy of the hippocampus and are common in asthma. However, minimal neuroimaging data are available in asthma patients. Methods: We conducted a retrospective analysis of 1, 287 adult participants from the Dallas Heart Study, an epidemiological sample of Dallas County residents. Study outcome variables were hippocampal volumes measured by FreeSurfer. ANOVA was used to examine a gender difference in hippocampal volumes. General Linear Models (GLM) were conducted to examine asthma diagnosis association with hippocampal volumes. Results: The prevalence rate of asthma among our study sample was 10.8% with 9.6% in males and 11.7% in females. After controlling for demographic characteristics, participants with asthma had significantly smaller total, right, and left hippocampal volumes than those without asthma. The association of asthma with smaller hippocampal volume was significant among males but not among females. Conclusion: Hippocampal volume in a large and diverse sample of adults was significantly smaller in people with asthma as compared to those without asthma. These findings suggest that asthma may be associated with structural brain differences. Thus, medical illnesses without obvious direct neurodegenerative or even vascular involvement can be associated with brain changes. Because the hippocampus is a brain region involved in memory formation, these findings may have implications for treatment adherence that could have important implications for asthma treatment. Study limitations are the reliance on a self-reported asthma diagnosis and lack of additional asthma clinical information.